2019
DOI: 10.1186/s13018-019-1207-9
|View full text |Cite
|
Sign up to set email alerts
|

Is platelet-rich plasma an ideal biomaterial for arthroscopic rotator cuff repair? A systematic review and meta-analysis of randomized controlled trials

Abstract: Background Recently, many authors have reported the effects of platelet-rich plasma (PRP) on rotator cuff repair. Whether PRP treatment during arthroscopic rotator cuff repair improves tendon healing rates or restores full function remains unknown. The purpose of this meta-analysis was to evaluate the clinical improvement and radiological outcomes of PRP treatment in patients undergoing arthroscopic rotator cuff repair. Methods PubMed, EMBASE, and the Cochrane Central R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 59 publications
1
36
0
1
Order By: Relevance
“…Many studies tested treatment of rotator cuff injuries and sPTRCT with PRP (see [25,26,[61][62][63][64][65][66][67] for the most recent systematic reviews, meta-analyses, and editorial comments in this regard). Earlier systematic reviews and meta-analyses showed no (or almost no) benefit of augmenting arthroscopic rotator cuff repair with PRP [61][62][63][64], but two very recent meta-analyses demonstrated that the use of PRP in rotator cuff repair resulted in improved functional outcomes, pain levels, and healing rates compared to control [65,66].…”
Section: Efficacy Of Treating Symptomatic Partial-thickness Rotator mentioning
confidence: 99%
“…Many studies tested treatment of rotator cuff injuries and sPTRCT with PRP (see [25,26,[61][62][63][64][65][66][67] for the most recent systematic reviews, meta-analyses, and editorial comments in this regard). Earlier systematic reviews and meta-analyses showed no (or almost no) benefit of augmenting arthroscopic rotator cuff repair with PRP [61][62][63][64], but two very recent meta-analyses demonstrated that the use of PRP in rotator cuff repair resulted in improved functional outcomes, pain levels, and healing rates compared to control [65,66].…”
Section: Efficacy Of Treating Symptomatic Partial-thickness Rotator mentioning
confidence: 99%
“…Many studies tested treatment of rotator cuff injuries and sPTRCT with platelet rich plasma (PRP) (see [50][51][52][53][54][55][56][57] for the most recent systematic reviews, meta-analyses and editorial comments in this regard). Whereas earlier systematic reviews and meta-analyses showed no (or almost no) benefit of augmenting arthroscopic rotator cuff repair with PRP [50][51][52][53], two very recent meta-analyses demonstrated that the use of PRP in rotator cuff repair resulted in improved functional outcomes, pain levels and healing rates compared to control [54,55].…”
Section: Efficacy Of Treating Symptomatic Partial-thickness Rotator mentioning
confidence: 99%
“…As a concentrated source of autologous platelets, PRP releases several different growth factors and other cytokines through degranulation that promote healing of bone and soft tissue. PRP biological effects depend on the activation of α-granules in platelet resulting in release of various high concentrative growth factors and depends on the reticulate fibrous cross-linking structure from fibrinogen [2]. Formed reticulate fibrous scaffold can support new tissues regeneration with various growth factors induction.…”
Section: Introductionmentioning
confidence: 99%